Power management system for smart microgrid considering meteorological and load demand data / Sam Koohikamali - Sam , Koohikamali (2015)
Integration of utility scaled solar electricity generator into power networks can negatively affect the performance of next generation smart grid. Rapidly changing output power of this kind is unpredictable and thus one solution is to mitigate it by short-term to mid-term electrical storage systems like battery. For this purpose, the battery storage system should be dispatched properly by a power management system (PMS) and hence the main objective of this work is to propose a PMS for smart microgrid (MG) applications. Microgrid refers to a cluster of generation, load, and energy storage units which can operate in grid-connected and/or in islanded modes. In this work, a smart microgrid system which consists of diesel, battery storage, and solar plants is suggested as well. Microgrid is able to supply its local load based on operator decision and decline the power oscillations caused by solar photovoltaic (PV) plant together with variable loads. An algorithm is also proposed which helps to precisely design the battery energy storage plant. A novel application of time domain signal processing approach (i.e. moving average filtering) to filter oscillating output power of the solar PV plant is presented as well. In this case, a power smoothing index (PSI) is formulated, which considers both load and generation, and used to dispatch the battery plant. A droop reference estimator to schedule generation is also introduced where diesel plant can share the local load with grid. A current control algorithm is designed as well which controls the active power smoothing index to ensure battery current magnitude is allowable. Microgrid along with its communication platform and PMS are simulated using PSCAD software. PMS is tested under different scenarios using real load profiles and meteorological data in Malaysia to verify the operational abilities of proposed MG. The results indicate that PMS can effectively manage the MG and satisfies both operator and demand sides.